Drug utilization study of antihypertensive drugs in hypertensive diabetic patients in a tertiary care hospital - Raikar, Shrinivas R.; Patil, Shivaraj B.; Raikar, Dayanand R.; Mantale, Nagendra (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes along with hypertension is a very common ailment afflicting millions of people worldwide. The socio-economic stress caused by the morbidity and mortality associated with it is mind boggling. Hence, this study was undertaken to study the utilization of antihypertensive drugs in hypertensive diabetic patients. Methods: A prospective study was conducted on 100 hypertensive diabetic patients aged between 18 and 90 years of either gender attending Basaveshwar Teaching and General Hospital, Kalaburagi. The data collected were statistically analyzed and presented as counts and percentages. Results: In our study, we found that majority (63%) were male patients and majority belonged to 51-70 years age group. The majority of the patients were prescribed angiotensin converting enzyme inhibitors (ACEIs) alone (19%), followed by a combination of ACEIs and calcium channel blockers (9%). The generic prescribing was only 23%, and patient’s knowledge of correct dosage was 64%. Conclusion: In this study, it has been observed that the antihypertensives drugs were prescribed rationally, but the generic prescribing was only 23% which is inappropriate prescribing behavior. Hence, physicians should be educated to prescribe drugs in the generic name so that the cost of drugs is reduced.